2018
DOI: 10.1038/s41598-018-27626-4
|View full text |Cite
|
Sign up to set email alerts
|

Administration of molecular hydrogen during pregnancy improves behavioral abnormalities of offspring in a maternal immune activation model

Abstract: The aim of the present study was to investigate long-term outcomes of the offspring in a lipopolysaccharide (LPS)-induced maternal immune activation (MIA) model and the effect of maternal molecular hydrogen (H2) administration. We have previously demonstrated in the MIA mouse model that maternal administration of H2 attenuates oxidative damage and neuroinflammation, including induced pro-inflammatory cytokines and microglial activation, in the fetal brain. Short-term memory, sociability and social novelty, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 83 publications
0
8
0
Order By: Relevance
“…In addition, hydrogen can also protect against spinal cord injury and a variety of brain injuries caused by ischemia, hypoxia, trauma, and hemorrhage. A clinical study of patients suffering from cerebral infarction reported that hydrogen inhalation improved imaging results, National Institutes of Health Stroke Scale scores used to quantify the severity of stroke, and physical therapy evaluations based on the Barthel Index [ 82 ]. A rat model of subarachnoid hemorrhage revealed the influence of hydrogen in lessening neurological deficits [ 83 ] and endothelial cell injury [ 84 ].…”
Section: Preventive and Therapeutic Applications Of H 2 mentioning
confidence: 99%
“…In addition, hydrogen can also protect against spinal cord injury and a variety of brain injuries caused by ischemia, hypoxia, trauma, and hemorrhage. A clinical study of patients suffering from cerebral infarction reported that hydrogen inhalation improved imaging results, National Institutes of Health Stroke Scale scores used to quantify the severity of stroke, and physical therapy evaluations based on the Barthel Index [ 82 ]. A rat model of subarachnoid hemorrhage revealed the influence of hydrogen in lessening neurological deficits [ 83 ] and endothelial cell injury [ 84 ].…”
Section: Preventive and Therapeutic Applications Of H 2 mentioning
confidence: 99%
“…Its concentration was approximately 0.6 ppm. HW had a content of >0.4 mM H 2 , as reported previously [15][16][17][18][49][50][51]. Anti-PDGFRÎČ antibody [Y92] (ab32570, lot no.…”
Section: Reagentsmentioning
confidence: 56%
“…The long-term safety of inhaled hydrogen gas in mice has already been reported [48]. Although several therapeutic and preventive effects for various obstetric diseases such as preterm labor [49], preeclampsia [50], fetal brain injury [16,51], and fetal lung injury [15] have been reported, these studies did not report short-term adverse effects. Fourth, it is already known that this method of prenatal H 2 administration increases the hydrogen concentration in fetal lungs [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Poly I:C (see Meyer 2014 for a review) and also with LPS exposure (Fortier et al, 2007;Romero et al, 2010;SimĂ”es et al, 2018;Swanepoel et al, 2018;Waterhouse et al, 2018;Wischhof et al, 2015) although some variables such as the species used (Imai et al, 2018), the prenatal period at which exposure occurs (Waterhouse et al, 2018) Figure 1, PUS seems to be counteracting LPS effects to some extent. Therefore, a stronger effect of LPS exposure might be needed to obtain a main effect of the maternal immune activation or an interaction between both factors.…”
Section: Glutamine Levels Were Reduced In the Left Striatum By Prenatmentioning
confidence: 99%